2013
DOI: 10.1093/nar/gkt732
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the evolutionary conserved DNA-binding specificities of WRKY transcription factors by molecular dynamics and in vitro binding assays

Abstract: WRKY transcription factors constitute a large protein family in plants that is involved in the regulation of developmental processes and responses to biotic or abiotic stimuli. The question arises how stimulus-specific responses are mediated given that the highly conserved WRKY DNA-binding domain (DBD) exclusively recognizes the ‘TTGACY’ W-box consensus. We speculated that the W-box consensus might be more degenerate and yet undetected differences in the W-box consensus of WRKYs of different evolutionary desce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
158
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(174 citation statements)
references
References 84 publications
14
158
2
Order By: Relevance
“…These bidirectional interaction possibilities could in turn cause the multi-TTG2/DNA aggregates in EMSA studies when using TTG2 instead of the WRKY18 DNA binding domain alone. TTG2 itself contains two WRKY domains and belongs to group1 of the WRKY family (Brand et al, 2013). Studies with the ELISA-DPI technique showed that generally both domains of WRKY33, another group 1 member, could bind DNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These bidirectional interaction possibilities could in turn cause the multi-TTG2/DNA aggregates in EMSA studies when using TTG2 instead of the WRKY18 DNA binding domain alone. TTG2 itself contains two WRKY domains and belongs to group1 of the WRKY family (Brand et al, 2013). Studies with the ELISA-DPI technique showed that generally both domains of WRKY33, another group 1 member, could bind DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with the ELISA-DPI technique showed that generally both domains of WRKY33, another group 1 member, could bind DNA. Nevertheless the binding of the cDBD (C-terminal domain) is stronger than of the nDBD (Brand et al, 2013). Whether both WRKY domains of TTG2 can bind to the two W-boxes remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…We tested in vitro DNA binding of the chimeric proteins in a DNAprotein interaction (DPI)-ELISA assay (Brand et al, 2010(Brand et al, , 2013 and in vivo transactivation activity in leaf protoplasts. Intriguingly, fusion of the BAM domain of BAM8 to the N-terminal part of BAM7 (BAM78) resulted in a protein that bound to the BBRE motif in vitro and activated reporter gene expression in protoplasts.…”
Section: The Enzyme-like Domains Of Bam7 and Bam8 Have Distinct Functmentioning
confidence: 99%
“…DNA binding properties of BZR1-BAM wild-type and mutated proteins were determined using the DPI-ELISA method as described before (Brand et al, 2010(Brand et al, , 2013. The amount of total protein input was normalized to the level of heterologous expressed protein (Supplemental Figure 9).…”
Section: Dpi-elisamentioning
confidence: 99%
“…We speculated that the W-box consensus might be more degenerate and yet undetected differences in the W-box consensus of WRKYs of different evolutionary descent exist. Simulation analysis was performed to explore differences in DNA-binding specificities 38 .…”
Section: Fig 4: the Structural And Folding Evolution Of Camelmentioning
confidence: 99%